Electrochemical microfluidic biosensor for the detection of CD4+ T cells - Katarzyna Białas; Hui Min Tay; Chayakorn Petchakup; Razieh Salimian; Stephen G. Ward; Mark A. Lindsay; Han Wei Hou; Pedro Estrela (Microsystems & Nanoengineering)
Abstract Since the onset of the HIV epidemic, assessing CD4+ T-cells has become a routine procedure for evaluating immune deficiency, with flow cytometry established as the gold standard. Over time, various strategies and platforms have been introduced to improve CD4+ cell enumeration, aiming to enhance the performance of diagnostic devices and bring the service closer to patients. These advancements are particularly critical for low-resource settings and point-of-care applications, where the excellent performance of flow cytometry is hindered by its unsuitability in such environments. This work presents an innovative electrochemical microfluidic device that, with further development, could be applied for HIV management in low resource settings. The setup integrates an electrochemical sensor within a PDMS microfluidic structure, allowing for on-chip electrode functionalization and cell detection. Using electrochemical impedance spectroscopy, the biosensor demonstrates a linear detection range from 1.25 × 105 to 2 × 106 cells/mL, with a detection limit of 1.41 × 105 cells/mL for CD4+ cells isolated from blood samples, aligning with clinical ranges for both healthy and HIV+ patients. The biosensor shows specificity towards CD4+ cells with negligible response to monocytes, neutrophils, and bovine serum albumin. Its integration with a microfluidic chip for sensor fabrication and cell detection, compact size, minimal manual handling, ease of fabrication, electrochemical detection capability, and potential for multiplexing together with the detection range make the device particularly advantageous for use in low-resource settings, standing out among other devices described in the literature. This study also investigates the integration of a microfluidic Dean Flow Fractionation (DFF) chip for cell separation.